2003
DOI: 10.1136/emj.20.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Would a prehospital practitioner model improve patient care in rural Australia?

Abstract: Background: Existing rural prehospital models have been criticised for being isolated from the healthcare system, and for following inflexible clinical protocols. Greater reliance on clinical judgement and informed decision making in the prehospital setting offer the potential to improve patient care. Methods: Soft systems methodology was used to develop and critically appraise the prehospital practitioner model as an alternative to existing models. This approach started from the philosophical viewpoint that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Positive impacts have been described in the form of inter-professional working, immediacy of treatment and referral, and high patient satisfaction. Limited economic data from the London Ambulance Service in 2003/2004(Department of Health, 2004a suggested a saving of £37 (USD 65) per case, with treatment of patients on scene equating to a reduced ED admission rate of 358 patients per ECP with a cost saving of £31,700 (USD 56,046) per ECP. Mason et al (2006) indicated that the mean cost of an ECP patient contact was £24 (USD 42) compared with an ED contact of £55 (USD 97), producing a saving of £31 (USD 55).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Positive impacts have been described in the form of inter-professional working, immediacy of treatment and referral, and high patient satisfaction. Limited economic data from the London Ambulance Service in 2003/2004(Department of Health, 2004a suggested a saving of £37 (USD 65) per case, with treatment of patients on scene equating to a reduced ED admission rate of 358 patients per ECP with a cost saving of £31,700 (USD 56,046) per ECP. Mason et al (2006) indicated that the mean cost of an ECP patient contact was £24 (USD 42) compared with an ED contact of £55 (USD 97), producing a saving of £31 (USD 55).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Cooper et al (2007a) identified cultural issues such as blue collar 'crew room' perspectives versus white collar professionalism; restricted ambulance codes of communication compared to the elaborate communication codes in medicine; varying educational levels; and poor collaborative links between, for example, health and social services. O'Meara (2003) also recognised the barriers to the development of such roles including education, attitude change, and relaxation of professional boundaries, issues which Cooper et al (2007a) suggest may be resolved in part, by appointment of clinical leads, degree level training, clinical supervision, and focussed task allocation/ dispatch. …”
Section: Discussionmentioning
confidence: 98%
“…This has previously been shown in relation to the management of wounds 10 and hypoglycaemia, 11 or a range of health problems arising in specific populations. 12 We provide evidence that ECPs are fulfilling a broader public health and primary care outreach role in the local community 13 in both rural and urban locations.…”
Section: Principal Findingsmentioning
confidence: 91%
“…38 Many countries around the world such as Australia and New Zealand are contemplating about adopting this system into their existing pre-hospital care system especially in rural areas where the gap between primary health care and pre-hospital care is obvious and bridging the gap is a public demand. 39,40 Current international EMS systems have varied features and practices but they all resemble the main models of EMS systems in one way or another. The aim of international EMS systems is to adapt a model that meets the local needs and targets with diverse cultural, political and financial factors of each individual community.…”
Section: Models Of International Emergency Medical Service (Ems) Systemsmentioning
confidence: 99%